2020
DOI: 10.1007/s11205-020-02470-0
|View full text |Cite
|
Sign up to set email alerts
|

The Factors Predicting Quality of Life Among Unemployed Adults: A Model Based on Salutogenic Approach

Abstract: Unemployment narrows the realization of individual potential and has a negative effect on the experiences and status of an individual, thereby weakening the quality of life. We explored meaningfulness, health and work ability as predictors of quality of life among unemployed adults. A total of 30,598 persons participated in nationwide Finnish Regional Health and Well-Being Study (N = 76,000) between January 2014 and January 2015. This study used data from 1158 unemployed or laid-off persons aged 20–65. Develop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 58 publications
0
6
0
1
Order By: Relevance
“…Karyawan perlu merasa bahwa pekerjaan yang mereka lakukan adalah suatu hal yang memiliki makna. Hult, Pietilä, & Saaranen (2020) menegaskan bahwa kebermaknaan mempengaruhi kualitas hidup. Pada orang tidak bekerja pengaruhnya sedikit lebih rendah dari orang yang memiliki pekerjaan (Hult, Pietilä, & Saaranen, 2019).…”
Section: Hasil Dan Pembahasanunclassified
“…Karyawan perlu merasa bahwa pekerjaan yang mereka lakukan adalah suatu hal yang memiliki makna. Hult, Pietilä, & Saaranen (2020) menegaskan bahwa kebermaknaan mempengaruhi kualitas hidup. Pada orang tidak bekerja pengaruhnya sedikit lebih rendah dari orang yang memiliki pekerjaan (Hult, Pietilä, & Saaranen, 2019).…”
Section: Hasil Dan Pembahasanunclassified
“…Previous studies showed CCS to have impaired HRQOL compared to the general population [ 9 , 10 ]. Several childhood diagnosis and sociodemographic factors were associated with impaired HRQOL in CCS [ 9 , 10 , 11 ]. In addition, late effects, such as cardiovascular or pulmonary dysfunction, were associated with poor HRQOL [ 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…An integrative definition of QoL has been proposed as a multi-scale, multidimensional concept (Wong, Yang, Yuen, Chang, & Wong, 2018) that contains interacting objective and subjective elements (Costanza et al, 2008;De Vries, J. and Van Heck, 1998). Life achievement, integrated well-being, autonomy, social inclusion, and social relationships resolve the individual's quality of life (Hult, Pietilä, & Saaranen, 2020) Women began to be involved in the workforce in the 1940s and added to the traditional norms of women as housewives and breadwinners (Moen, 1992). The motivation of women to work is to earn income, have adequate social capital, and have stable and satisfying work.…”
Section: Introductionmentioning
confidence: 99%